Cervical lymph node metastasis from early-stage squamous cell carcinoma of the oral tongue. (May 2013) - Yuasa-Nakagawa, Keiko; Shibuya, Hitoshi; Yoshimura, Ryoichi; Miura, Masahiko; Watanabe, Hiroshi; Kishimoto, Seiji; Omura, Ken
Abstract Conclusions: The findings of this study demonstrated that the wait-and-watch strategy for neck metastasis from squamous cell carcinoma (SCC) of oral tongue is a reliable option and that salvage by surgical treatment is effective. However, younger patients should be closely monitored for recurrence. Adjuvant therapy may be recommended for patients with pathologically advanced disease. Objectives: Metastatic involvement of cervical lymph nodes is the most important prognostic indicator in patients with oral tongue SCC. With the objective of determining the most appropriate treatment strategy for regional recurrence, we conducted a retrospective review of clinicopathologic factors. Methods: The clinicopathologic features of 103 patients with oral tongue SCC, in whom the local lesions were treated successfully by low-dose interstitial brachytherapy (LD-IBT), but who subsequently developed cervical lymph node metastases and were treated by salvage surgery, were reviewed. Results: In the patients who underwent surgical treatment at our hospital, 5-year disease-free survival and regional control rates were 69.3% and 85.3%, respectively. The clinicopathologic factors significantly associated with unfavorable disease-free survival were the presence of extracapsular spread (hazard ratio (HR) = 3.005, p = 0.045), multiple and large lymph nodes (HR = 2.850, p = 0.010 and HR = 3.112, p = 0.007, respectively), younger age (HR = 2.429, p = 0.048), and shorter interval from the LD-IBT to detection of neck metastasis (HR = 1.749, p = 0.013).